Coplanar Polychlorinated Biphenyls Impair Glucose Homeostasis in Lean C57BL/6 Mice and Mitigate Beneficial Effects of Weight Loss on Glucose Homeostasis in Obese Mice - Baker, Nicki A. (National Institute of Environmental Health Sciences, 2012)
Background: Previous studies demonstrated that coplanar polychlorinated biphenyls (PCBs) promote proinflammatory gene expression in adipocytes. PCBs are highly lipophilic and accumulate in adipose tissue, a site of insulin resistance in persons with type 2 diabetes. Objectives: We investigated the in vitro and in vivo effects of coplanar PCBs on adipose expression of tumor necrosis factor α (TNF-α) and on glucose and insulin homeostasis in lean and obese mice. Methods: We quantified glucose and insulin tolerance, as well as TNF-α levels, in liver, muscle, and adipose tissue of male C57BL/6 mice administered vehicle, PCB-77, or PCB-126 and fed a low fat (LF) diet. Another group of mice administered vehicle or PCB-77 were fed a high fat (HF) diet for 12 weeks; the diet was then switched from HF to LF for 4 weeks to induce weight loss. We quantified glucose and insulin tolerance and adipose TNF-α expression in these mice. In addition, we used in vitro and in vivo studies to quantify aryl hydrocarbon receptor (AhR)-dependent effects of PCB-77 on parameters of glucose homeostasis. Results: Treatment with coplanar PCBs resulted in sustained impairment of glucose and insulin tolerance in mice fed the LF diet. In PCB-77–treated mice, TNF-α expression was increased in adipose tissue but not in liver or muscle. PCB-77 levels were strikingly higher in adipose tissue than in liver or serum. Antagonism of AhR abolished both in vitro and in vivo effects of PCB-77. In obese mice, PCB-77 had no effect on glucose homeostasis, but glucose homeostasis was impaired after weight loss. Conclusions: Coplanar PCBs impaired glucose homeostasis in lean mice and in obese mice following weight loss. Adipose-specific elevations in TNF-α expression by PCBs may contribute to impaired glucose homeostasis.